Epidemiological, Clinical and Laboratory characteristics of acute disseminated encephalomyelitis in children: a retrospective study - Taghdiri, Mohammad-Mahdi; Hassanvand amouzadeh, Masoud; Esmail Nejad, Shaghayegh Sadat; Abasi, Ezatollah; Alipour, Abbas; Akhavan sepahi, Mohsen (Iranian Journal of Child Neurology, 2019)
We aimed to study the precipitating factors, demographic data, clinical and radiological manifestations, electroencephalography and laboratory findings, as well as association with infections, immunization and incidence of relapse of acute disseminated encephalomyelitis (ADEM) in children admitted to Mofid Children Hospital, Tehran, Iran from Mar 2013 to Mar 2016. Materials & Methods A 3-yr retrospective review of 29 children with definite final diagnosis of ADEM in Mofid Hospital in Tehran, Iran was performed. The diagnosis was based on specified criteria, including a presumed acute demyelinating process with no history of unexplained neurological symptoms and at least one demyelinating lesion shown on magnetic resonance imaging without evidence of previous destructive white matter lesions. Results Overall, 29 children diagnosed as ADEM were studied in terms of demographic characteristics, clinical manifestations and laboratory findings in two groups according to their recurrence. The mean age of the patients with recurrence was less than those without it were. It was more common in females but the difference was not statistically meaningful. There was no relationship between the season of the first episode of the disease and the recurrence incidence. Moreover, the relationship between viral infections and recurrence was statistically non-meaningful. No relationship between the recurrence of ADEM and clinical manifestations, radiological and laboratory findings was found. Conclusion The reason for high rate of recurrence in our patients may be related to the younger age of children in our study. .